Contra Legem Pembagian Harta Bersama Perspektif Maslahah Murshalah - Zuhriandi, Novrizal; Lubis, Fauziah; Nurcahaya, Nurcahaya (Kamaya: Jurnal Ilmu Agama, 2023)
Of the many impacts that occur from the breakdown of a marriage, one of them is the problem of dividing joint assets. Where joint assets are assets acquired by a husband and wife while they were still married. In decision NO.2802/Pdt.G/2018/PA.Dpk, the Depok Religious Court Judge gave a larger share of joint assets to the ex-wife, with details of 70% for the ex-wife and 30% for the ex-husband. Meanwhile, Article 97 of the Compilation of Islamic Law explicitly provides for shares of joint assets in equal amounts between the wife and husband. Where the judge clearly ignored written Material Law, namely the Compilation of Islamic Law, in deciding the case. This research aims to find out the basic considerations of the Depok Religious Court judges in deciding this case, and how the KHI and Islamic law are reviewed from Maslahah Murshalah's perspective on resolving the joint property problem. This research is normative juridical research. This type of research is library research. The results of the research illustrate that the judge decided the case by giving a share of joint assets in both the Convention and Reconvention decisions in the amount of 30% for the Convention Plaintiff/Reconvention Defendant and 70% for the Convention Defendant/Reconvention Plaintiff. In this decision the judge adopted jurisprudence, more precisely, Supreme Court Decision No.266/K/AG/2010 as a legal consideration in deciding the case, however the judge also made legal discoveries using independent legal methods in determining the amount obtained by each partner, because in In this decision, the judge did not fully adopt the Supreme Court's jurisprudence, but rather, chose to dig deeper into the ins and outs of the assets, roles and contributions of the couple during the marriage period.